Green space exposure’s influence on mental well-being during COVID-19 campus lockdowns: a satisfaction mediating pathway - Zhou, Shaoyou; Wang, Shiqi; Liu, Haonan (Journal of Environmental Engineering and Landscape Management, 2024)
Recent research indicates that exposure to green space may have positive effects on the mental health of students, potentially mediated by factors such as environmental satisfaction and social cohesion. However, the specific impact of green space exposure on students’ mental health during the COVID-19 campus lockdowns unexplored. To investigate this relationship, a survey was conducted via social media among 346 current students residing on a locked-down campus, assessing their mental well-being, green space satisfaction, social environment satisfaction, subjective exposure and objective exposure to green space. A structural equation model (SEM) was employed to examine the relationships among various dimensions of green space exposure, satisfaction and students’ mental well-being. The findings indicate that subjective exposure to green space has a positive impact on mental well-being and indirectly through social environment satisfaction. Additionally, objective exposure could indirectly influence mental well-being through green space satisfaction and social environment satisfaction.